Cholinergic profiles in the Goettingen miniature pig (Sus scrofa domesticus) brain. Issue 3 (30th August 2016) - Mahady, Laura J.; Perez, Sylvia E.; Emerich, Dwaine F.; Wahlberg, Lars U.; Mufson, Elliott J.
Abstract : Central cholinergic structures within the brain of the even‐toed hoofed Goettingen miniature domestic pig ( Sus scrofa domesticus ) were evaluated by immunohistochemical visualization of choline acetyltransferase (ChAT) and the low‐affinity neurotrophin receptor, p75 NTR . ChAT‐immunoreactive (‐ir) perikarya were seen in the olfactory tubercle, striatum, medial septal nucleus, vertical and horizontal limbs of the diagonal band of Broca, and the nucleus basalis of Meynert, medial habenular nucleus, zona incerta, neurosecretory arcuate nucleus, cranial motor nuclei III and IV, Edinger‐Westphal nucleus, parabigeminal nucleus, pedunculopontine nucleus, and laterodorsal tegmental nucleus. Cholinergic ChAT‐ir neurons were also found within transitional cortical areas (insular, cingulate, and piriform cortices) and hippocampus proper. ChAT‐ir fibers were seen throughout the dentate gyrus and hippocampus, in the mediodorsal, laterodorsal, anteroventral, and parateanial thalamic nuclei, the fasciculus retroflexus of Meynert, basolateral and basomedial amygdaloid nuclei, anterior pretectal and interpeduncular nuclei, as well as select laminae of the superior colliculus. Double immunofluorescence demonstrated that virtually all ChAT‐ir basal forebrain neurons were also p75 NTR ‐positive. The present findings indicate that the central cholinergic system in the miniature pig is similar to other mammalian species. Therefore, the miniature pig may be an appropriate animal model for preclinical studies of neurodegenerative diseases where the cholinergic system is compromised. J. Comp. Neurol. 525:553–573, 2017. © 2016 Wiley Periodicals, Inc. Abstract : We examined the distribution of choline acetyltransferase (ChAT) immunohistochemistry in the Goettingen miniature pig ( Sus scrofa domesticus ) forebrain and midbrain. The pig brain displays a similar distribution of cholinergic profiles to other mammals, making it a suitable large animal model for the study of cholinergic system disorders. In this illustration we show ChAT immunoreactive profiles in the Edinger‐Westphal (EW), oculomotor (IIIn), and trochlear (IVn) nuclei (A, B), interpeduncular nucleus (C), and select laminae of the superior colliculus (D) in the Goettingen miniature pig brain.